Weight gain and supplemental O2: Risk factors during the hematopoietic cell transplant admission in pediatric patients. Issue 11 (25th April 2017) - Rowan, Courtney M.; Nitu, Mara E.; Moser, Elizabeth A. S.; Swigonski, Nancy L.; Renbarger, Jamie L.
Abstract: Background: Respiratory failure in the pediatric hematopoietic cell transplant (HCT) recipient is the leading cause for admission to the intensive care unit and carries a high mortality rate. The objective of this study is to investigate the association of clinical risk factors with the development of respiratory failure in the pediatric allogeneic HCT recipient. Procedures: This is a single‐center, retrospective review of allogeneic pediatric HCT from 2008 to 2014. Multiple variables were examined. The primary outcome was respiratory failure. Percent weight gain was investigated at multiple time points. Bivariate and multivariate regression was used. Results: Of the 87 allogeneic HCT recipients, 22 (25%) developed respiratory failure. Mortality for entire cohort was 13.8%. All who died were intubated prior to death. The group with respiratory failure had significantly higher percent weight gain increase at multiple time points: peak weight prior to discharge or intubation ( P = 0.008), weight at discharge or intubation ( P = .001), and weight at day 43 (median day for intubation) ( P = 0.02). Odds ratio (OR) for respiratory failure increased with increasing percentage peak weight gain: 10% increase (3.1 [1.1, 9.0]), 15% increase (4.1 [1.5, 11.2]), and 20% (8.3 [2.4. 28.9]). Fifty percent of all patients required supplemental O2 . OR for respiratory failure in patients requiring more than 1 l supplemental O2 is 25.3 (6.5, 98.7). Conclusion: Percent weight gain and need for supplemental oxygen is highly associated with the development of respiratory failure in pediatric HCT recipients, representing predictors of acute respiratory failure in pediatric HCT. These data could be incorporated into an algorithm that should be developed, implemented, and validated in a prospective, multicenter fashion.